Prison ethnography by correspondence? - Jardine, Cara (Criminology & criminal justice, 2024)
Prison ethnography offers researchers a unique vantage point from which to explore the relationships, power dynamics, degradations, solidarities and sensory assaults which occur within the prison walls. Yet, despite the valuable insights to be gained from this methodological approach, prison ethnographies can be extremely challenging to conduct. Institutional pressures arising from both the prison and the contemporary University pose considerable obstacles for researchers, and the outbreak of Covid-19 has heightened these barriers further still. This article will argue that the methodology of cultural probes can preserve at least some of the ethos of ethnographic research when conducting research by correspondence. It will reflect on the methodological and ethical challenges of this approach, and critically discuss its potential to offer a more participatory and less extractive means for researching the nuances of prison life while collecting data from a distance.